IMPROVING STUDENTS’ SPEAKING ABILITY IN DESCRIBING LOCAL TOURISM OBJECTS THROUGH PROJECT-BASED LEARNING TECHNIQUE - Utari Dwi Sartika (Corolla International Conference, 2022)
The aim of this research is to find out how does Project-Based Learning Technique improve the students’ speaking ability. In SMKN 1 Kota Bengkulu, the students still have low motivation especially in speaking activities, they do not understand many aspects in speaking English, because the teacher use monotous activities and need more interesting strategy in English class. This research applied Classroom Action Research (CAR) method. The respondents of this research were the tenth grade students of Tourism Department (X PJP 2 Class) of SMKN 1 Kota Bengkulu that consisted of 26 students. The result showed that Project-Based Learning Technique can improve the students’ speaking ability in describing local tourism objects at the tenth grade students of Tourism Departmen of SMKN 1 Kota Bengkulu. The improvement was showed by the students’ average score in preassessment test (63.65) that included into “Moderate” category; and average score in cycle II test was (75.23) that included into “Good” category. It means that the students got (11.58) point of improvement after getting actions for two cycles. The most important progress for students were learning atmosphere in the classroom got better, especially in students’ attitude, learning motivation, and classroom interaction. During the classroom, most of the students have avoided doing indiscipline activities like chatting with friends and doing other activities. The students looked so curious to learn this new teaching technique and paid serious attention to the teacher’s explanation. In group activities, the students involved actively giving their contribution in overcoming problems in their group.